<h3>
Answer: -7 < x < 17</h3>
====================================================
Explanation:
Plug in the lower bound of the domain, which is x = -3
f(x) = 3x+2
f(-3) = 3(-3)+2
f(-3) = -9+2
f(-3) = -7
If x = -3, then the output is y = -7. Since f(x) is an increasing function (due to the positive slope), we know that y = -7 is the lower bound of the range.
If you plugged in x = 5, you should find that f(5) = 17 making this the upper bound of the range.
The range of f(x) is -7 < y < 17
Recall that the domain and range swap places when going from the original function f(x) to the inverse ![f^{-1}(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29)
This swap happens because how x and y change places when determining the inverse itself. In other words, you go from y = 3x+2 to x = 3y+2. Solving for y gets us y = (x-2)/3 which is the inverse.
-----------------------
In short, we found the range of f(x) is -7 < y < 17.
That means the domain of the inverse is -7 < x < 17 since the domain and range swap roles when going from original to inverse.
Answer:
-1/3
Step-by-step explanation:
Answer:
I think the first one is power ( if not then coefficient) and the second is definitely expression
Step-by-step explanation:
<span>(-2, y1), (6, 7) Slope = 1/2
slope = (y2-y1)/(x2-x1)
1/2 = (7 - y1) / (6 - -2)
1/2 = (7-y1) / 8
7-y1 = 8/2
7-y1 = 4
y1 = 7 - 4
y1 = 3
Answer: </span><span>(-2, 3), (6, 7) with Slope = 1/2
</span>proof:
slope = (y2-y1)/(x2-x1)
slope = (7 - 3) / (6 - -2)
slope = 4/8
slope = 1/2